Pendidikan Kesehatan tentang Pemeriksaan Triple Elimination pada Ibu Hamil Di Puskesmas Seririt II - Ketut Eka Larasati Wardana; Yopita Triguno (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2022)
Background: Pregnant woman are one the of the populations at risk of contracting HIV/AIDS, Hepatitis B, and Syphiis. More than 90% of chidren who have HIV, Syphilis and Hepatitis B infections, are infected their mothers. Efforts are needed to break the chain of transmissions examination. Purpose: to educate pregnant women about the Triple Elimination examination. The methods used in this activity are lectures, pretest-postest, discussions, and counseling. Results: there is an increase in knowledge between before and after counseling is given. Conclusion: counseling activities about triple elimination examination in pregnant women can increase pregnant women's knowledge about blood tests during pregnancy. This activity also contributes to the success of government programs in preventing danger signs during pregnancy.